Structural impact of proline mutations in the loop region of an ancestral membrane protein. Issue 1 (January 2016) - Nadeau, Vincent G.; Deber, Charles M.
ABSTRACT: The sodium ion‐translocating F0 F1 ATP synthase from the bacterium Ilyobacter tartaricus contains a highly stable rotor ring composed of 11 c subunits. The synthase subunit c—in effect an 89‐residue peptide that folds into a helical hairpin consisting of two membrane‐spanning helices and a cytoplasmic loop—was probed for the structural impact of a series of substitutions with the β‐turn‐inducing proline‐glycine couplet scanning the hairpin loop (residues 44‐51) of the I. tartaricus sequence. We found that a Pro residue in other than the wild type position 47 alters the gross secondary structure of subunit c from α‐helical to β‐sheet‐like, as well as changing its oligomeric ring structure, and its stability toward heat and trichloroacetic acid treatment. Such a Pro‐mediated structural switch in one of the first membrane proteins in life hints to a potential evolutionary connection between α‐helical and β‐sheet membrane proteins. © 2015 Wiley Periodicals, Inc. Biopolymers (Pept Sci) : 37–42, 2016.